2017
DOI: 10.1111/jpn.12636
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding frequency on meat quality traits and Longissimus muscle proteome in finishing pigs

Abstract: Sixty-four barrows with an initial body weight of 59.8 ± 2.1 kg were allocated to one of the two feeding frequency regimes (had free access to diet and fed two meals per day). Pigs had free access (FA) to feed were fed on an ad libitum basis during the 8-week experimental period. Pigs fed twice daily (M2) were allowed to consume their meals in 2 h. Pigs fed twice daily had lower average daily feed intake (p < 0.01) and average daily gain (p < 0.1), but a greater G:F (p < 0.05) than FA pigs. Lower perirenal fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Previous studies have shown that the biphasic feeding regimen improved the feed efficiency of pigs which were associated with altered energy partitioning and storage form (protein or lipid), as indicated by higher lean tissue content and/or decreased fat deposition in biphasic-fed pigs ( Newman et al, 2014 ; Liu et al, 2017 ; Yan et al, 2020 ). Gut microbiota have been recognized as a critical factor influencing the energy partitioning between lean and fat tissues of the host ( Bäckhed et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the biphasic feeding regimen improved the feed efficiency of pigs which were associated with altered energy partitioning and storage form (protein or lipid), as indicated by higher lean tissue content and/or decreased fat deposition in biphasic-fed pigs ( Newman et al, 2014 ; Liu et al, 2017 ; Yan et al, 2020 ). Gut microbiota have been recognized as a critical factor influencing the energy partitioning between lean and fat tissues of the host ( Bäckhed et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, feeding frequency has been regarded as a critical factor that affects weight and carcass composition in pigs ( Le Naou et al, 2014 ). Some studies have demonstrated that reducing meal frequency impaired the feed efficiency, while other studies contend that reduced meal frequency elevated the feed efficiency of pigs ( Schneider et al, 2011 ; Colpoys et al, 2016 ; Liu et al, 2017 ). A previous study has shown that the duration of each feeding bout is critical for the improvement effect of reduced meal frequency on feed conversion efficiency ( Newman et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A twelve meals regimen increased the liver concentration of total lipid, glycogen, and triglyceride than that in the two meals daily pigs [8]. Compared with pigs fed ad libitum, the activities of citrate synthase, β-hydroxylacyl-CoA dehydrogenase, and lactate dehydrogenase were greater in the longissimus muscle of the two meals daily regimen [9]. The intestine and liver are the major digestive, absorption, and metabolism organs of the body and play a key role in the metabolism of nutrients [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The results presented above indicated that the level of ALD could be another significant factor in muscle glycolysis after slaughter beside other enzymes (e.g., phosphofructokinase, glycogen phosphorylase) (Apaoblaza et al, ; England et al, ). Moreover, Liu, Cai, Xiong, and Zhang () demonstrated a significant influence of feeding frequency regimes of pigs (free access to diet and feeding twice a day) on proteome of Longissimus muscle. The results showed that energy expenditure was increased by reducing meal frequency.…”
Section: Discussionmentioning
confidence: 99%